2019
DOI: 10.22460/ceria.v2i5.p276-285
|View full text |Cite
|
Sign up to set email alerts
|

IMPLEMENTATION OF STEAM (Science Technology Engineering Art Mathematics) - BASED EARLY CHILDHOOD EDUCATION LEARNING IN SEMARANG CITY

Abstract: Learning in Early Childhood Education (ECE) today should adjust the 21st century competency framework. In this case, learning innovation is needed to actualize a generation that is creative, innovative, critical thinking, able to communicate and collaborate. STEAM (Science Technology Engineering Art Mathematics) - based ECE learning is currently seen as an approach that aims to stimulate creativity and  prepare children in a world of work that is full of innovation and invention. Research shows that there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
20

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 0 publications
2
22
0
20
Order By: Relevance
“…Pendidikan sangat penting untuk memberdayakan anak-anak dalam mengembangkan potensi dirinya (Munawar, dkk, 2019). Masih banyak anak-anak usia dini di Indonesia yang belum mampu untuk mengembangkan bagaimana cara untuk menyelesaikan suatu permasalahan yang kecil pada dirinya, bagaimana cara berpikir kritis dan meningkatkan kreativitas serta komunikasinya.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Pendidikan sangat penting untuk memberdayakan anak-anak dalam mengembangkan potensi dirinya (Munawar, dkk, 2019). Masih banyak anak-anak usia dini di Indonesia yang belum mampu untuk mengembangkan bagaimana cara untuk menyelesaikan suatu permasalahan yang kecil pada dirinya, bagaimana cara berpikir kritis dan meningkatkan kreativitas serta komunikasinya.…”
Section: Pendahuluanunclassified
“…Dalam engineering anak dapat membangun pikiran dan perasaan dalam kegiatan sehari-hari dan juga dapat menstimulasi aspek-aspek perkembangan seperti kognitif, bahasa, emosional, fisik motorik, dan seni (Wahyuningsih dkk, 2020). Pada konten engineering juga menstimulasi kemampuan anak usia dini dalam merangkai dan membangun suatu bentuk tertentu menggunakan media yang relevan (Munawar dkk, 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Seperti yang dijelaskan oleh Kofac (2017) bahwa STEAM memuat pembelajaran berbasis teknologi ilmiah dan kemampuan dalam memecahkan masalah di dunia nyata. Selain itu dengan model pembelajaran STEAM mendorong anak untuk mengembangkan rasa ingin tahu, keterbukaan pengalaman (Perignat & Katz-Buonincontro, 2019) dan mengajukkan pertanyaan sehingga anak membangun pengetahuan disekitarnya dengan mengeksplorasi, mengamati, menemukan, dan menyelidiki sesuatu yang ada disekitarnya (Munawar, 2019). Fokus STEAM adalah pada menciptakan yaitu produk akhir dan proses pembuatan.…”
Section: Hasil Dan Pembahasanunclassified
“…From some of these opinions, it can be concluded that critical thinking skills are high-level abilities of a student, even though these thinking skills are not owned by all students, critical thinking skills can be trained and raised through various learning processes [2] [18]. Furthermore, Munawar, et al [19] and Akhdinirwanto, et al [20] stated that "the ability to think critically is a thought process that uses the ability to analyze arguments and give opinions based on logical reasoning. Critical thinking indicators consist of providing simple explanations, building basic skills, making references, providing further explanations, and setting strategies and tactics [11].…”
Section: Introductionmentioning
confidence: 99%